Freelancer Auditor Practices from a Legal Perspective: Risk and Compliance Analysis in the Indonesian Regulatory Framework - Ahmad Muzamil; M. Shidqon Prabowo; Takwim Azami (JURNAL AKTA, 2025)
The audit profession plays a vital role in ensuring transparency, accountability, and reliability of financial information. Globally, the emergence of freelance auditors reflects market demand for flexible and cost-efficient audit services. However, in Indonesia, audit services are strictly regulated and legally limited to licensed public accountants and public accounting firms, creating tension between regulatory requirements and market needs. This study aims to analyze the legal framework governing audit practices in Indonesia, examine the implementation challenges related to freelance auditor practices, and formulate regulatory strengthening mechanisms to ensure legal certainty and professional accountability. The study employs a normative juridical research method, using qualitative descriptive analysis of primary legal materials, including Law Number 5 of 2011, Government Regulation Number 20 of 2015, and Financial Services Authority Regulation Number 9 of 2023, supported by secondary literature and comparative studies. The findings indicate that freelance auditor practices have no legal basis in Indonesia and arise primarily due to the limited capacity of licensed public accountants relative to market demand. This situation poses risks to legality, audit quality, and accountability. Freelance auditing is an unrecognized legal practice arising from market demand that must be addressed through stronger regulation and professional capacity.